The Determinants of Transfer Pricing in Energy Sector Companies Listed on the Indonesian Stock Exchange - Kusbandiyah, Ani; Fakhruddin, Iwan; Mudjiyanti, Rina; Priyanto, Eko (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study examines